Visuospatial Deficits Are Associated with Pisa Syndrome and not Camptocormia in Parkinson's Disease. Issue 1 (14th November 2022) - Artusi, Carlo Alberto; Montanaro, Elisa; Erro, Roberto; Margraf, Nils; Geroin, Christian; Pilotto, Andrea; Magistrelli, Luca; Spagnolo, Francesca; Marchet, Alberto; Sarro, Lidia; Cuoco, Sofia; Sacchetti, Marta; et al.
ABSTRACT: Background: Pisa syndrome (PS) and camptocormia (CC) are postural abnormalities frequently associated with Parkinson's disease (PD). Their pathophysiology remains unclear, but the role of cognitive deficits has been postulated. Objectives: To identify differences in the neuropsychological functioning of patients with PD with PS or CC compared with matched patients with PD without postural abnormalities. Methods: We performed a case‐control study including 57 patients with PD with PS (PS+) or CC (CC+) and 57 PD controls without postural abnormalities matched for sex, age, PD duration, phenotype, and stage. Patients were divided into four groups: PS+ (n = 32), PS+ controls (PS−, n = 32), CC+ (n = 25), and CC+ controls (CC−, n = 25). We compared PS+ versus PS− and CC+ versus CC− using a neuropsychological battery assessing memory, attention, executive functions, visuospatial abilities, and language. Subjective visual vertical (SVV) perception was assessed by the Bucket test as a sign of vestibular function; the misperception of trunk position, defined as a mismatch between the objective versus subjective evaluation of the trunk bending angle >5°, was evaluated in PS+ and CC+. Results: PS+ showed significantly worse visuospatial performances ( P = 0.025) and SVV perception ( P = 0.038) than their controls, whereas CC+ did not show significant differences compared with their control group. Reduced awareness of postural abnormality was observed in >60% of patients with PS or CC. Conclusions: Low visuospatial performances and vestibular tone imbalance are significantly associated with PS but not with CC. These findings suggest different pathophysiology for the two main postural abnormalities associated with PD and can foster adequate therapeutic and prevention strategies.